Prescription for natural cures : a self-care guide for treating health problems with natural remedies including diet, nutrition, supplements, and other holistic methods - Balch, James F., 1933-; Stengler, Mark.; Young-Balch, Robin (Hoboken : Wiley, 2011)
"The new edition of this invaluable guide has been thoroughly updated to reflect the very latest research and recommendations. This revised edition prescribes remedies for almost 200 conditions, including 20 new entries such gluten sensitivity and MRSA. You'll find easy-to-understand discussions of the symptoms and root causes of each health problem along with a proven, natural, customized prescription that may include supplements, herbal medicine, homeopathy, aromatherapy, Chinese medicine, hydrotherapy, bodywork, natural hormones, and other natural cures in addition to nutritional advice"--
Machine generated contents note: Preface. -- Acknowledgements. -- How to Use This Book. -- Part One: Conditions. -- Abscesses and Boils. -- Acne. -- Aging. -- AIDS and HIV. -- Alcoholism. -- Allergies. -- Alzheimer's Disease. -- Anemia. -- Angina. -- Anorexia Nervosa. -- Anxiety. -- Arteriosclerosis. -- Arthritis. -- Asthma. -- Athlete's Foot. -- Attention-Deficit-Hyperactivity Disorder. -- autism. -- Back Pain. -- Bad Breath (Halitosis). -- Bee Stings. -- Bladder Infection (Cystitis). -- Blood Pressure, High. -- Bone Fractures. -- Brittle Nails. -- Bronchitis. -- Bruises. -- Bulimia. -- Burns (including Sunburn). -- Cancer. -- Candidiasis (Thrush and Yeast Infection). -- Cardiovascular Disease. -- Carpal Tunnel Syndrome (CTS). -- Cataracts. -- Cervical Dysplasia. -- Cholesterol, High. -- Chronic Fatigue Syndrome (CFS). -- Colic. -- Common Cold. -- Constipation. -- Cough. -- Crohn's Disease. -- Cystitis. -- Depression. -- Diabetes. -- Diarrhea. -- Diverticulitis. -- Dizziness. -- Drug Addiction. -- Ear Infection. -- Eating Disorders (Anorexia Nervosa and Bulimia). -- Eczema. -- Endometriosis. -- Fever. -- Fibrocystic Breasts. -- Fibroids, Uterine. -- Fibromyalgia. -- Flu. -- Food Allergies/Sensitivities. -- Food Poisoning. -- Gallbladder Problems. -- Gastritis. -- Gingivitis. -- Glaucoma. -- Gluten Sensitivity. -- Gout. -- Hair Loss. -- Halitosis. -- Headache. -- Hearing Loss. -- Hemorrhoids. -- Heart Attack and Heart Disease. -- Hepatitis. -- Herpes. -- Herpes Zoster. -- Hiatal Hernia and Acid Reflux Disease. -- High Blood Pressure. -- High Cholesterol. -- HIV. -- Hives. -- Hyperthyroidism. -- Hypoglycemia. -- Hypothyroidism. -- Impotence. -- Infertility. -- Influenza. -- Insomnia. -- Irritable Bowel Syndrome. -- Jet Lag. -- Kidney Stones. -- Lupus. -- Macular Degeneration. -- Memory Problems. -- Menopause. -- Motion Sickness. -- MRSA. -- Multiple Sclerosis. -- Muscle Aches and Cramps. -- Obesity. -- Osteoporosis. -- Parasites. -- Parkinson's Disease. -- Poisoning. -- Pregnancy-Related Problems. -- Premenstrual Syndrome (PMS). -- Prostate Enlargement (Benign Prostatic Hyperplasia). -- Prostatitis. -- Psoriasis. -- Rosacea. -- Seasonal Affective Disorder (SAD). -- Shingles (Herpes Zoster). -- Sinusitis. -- Sore Throat. -- Sprains and Strains. -- Stroke. -- Substance Abuse (Drug and Alcohol Addiction). -- Syndrome X. -- TMJ (Temporomandibular Joint) Syndrome. -- Thrush. -- Tinnitus. -- Underactive Thyroid. -- Ulcers. -- Uterine Fibroids. -- Vaginitis. -- Varicose Veins. -- Vertigo. -- Warts. -- Yeast Infection. -- Part Two: The Essentials of Natural Medicine. -- Diet and Nutrition. -- Fasting. -- Nutritional Supplements. -- Herbal Medicine. -- Homeopathy. -- Aromatherapy. -- Traditional Chinese Medicine: Acupuncture and Acupressure. -- Hydrotherapy. -- Natural Hormones. -- Bodywork. -- Exercise and Stress Reduction. -- Part Three: Appendix. -- A Natural Health-Care Modalities and Resource Guide. -- Glossary. -- Index. -- About the Authors.
Includes bibliographical references and index.
Keywords: Naturopathy -- Popular works; Alternative medicine -- Popular works; Self-care, Health; HEALTH & FITNESS / General